Factors influencing mussel (Mytilus galloprovincialis) nutritional quality. (September 2019) - Grkovic, N; Dimitrijevic, M; Teodorovic, V; Karabasil, N; Vasilev, D; Stajkovic, S; Velebit, B
Abstract: Mussels display interesting nutritional characteristics as they are a rich source of proteins, carbohydrates and minerals and provide an almost unlimited variety of fatty acids with beneficial roles in human health. The quality characteristics of Mytilus galloprovincialis mussels harvested at seasonal intervals reflect the different environmental conditions met by the animals during their growth. Their chemical composition is strictly dependent on the phytoplankton resources available and, therefore, on the season of harvest. Parameters such as water temperature, food availability and the gametogenesis cycle can influence the meat yields and the biochemical composition of the mussels, conditioning their commercial quality and organoleptic characteristics. In order to determine the nutritional value of blue mussels, it is of great relevance to identify their biochemical composition as well as the most favourable season and geographical location for mussel-harvesting. That data could be useful to indicate the periods of the year more suitable for the marketing and consumption of mussels.